Switch Costs Occur at Lemma Stage When Bilinguals Name Digits: Evidence from Language-Switching and Event-Related Potentials - Chang, Song; Xie, Jiushu; Li, Li; Wang, Ruiming; Liu, Ming (Frontiers in Psychology, 2016)
Switch costs are generally found in language switching tasks. However, the locus where switch costs occur during bilingual language production remains unclear. Several studies that used a cued language-switching paradigm have attempted to investigate this question in bilingual language production, but researchers have not reached a consensus. Moreover, we are interested in where switch costs occur when language selection occurs after lemma activation. Previous studies have not investigated this question because most previous studies presented language cues before or along with the stimuli. Therefore, we used a modified cued language-switching paradigm with a combined event-related potential (ERP) technique to explore the locus of swtich costs during bilingual language production. The cue and stimulus were separated and presented in two different presentation sequences in which Indonesian-Chinese bilingual speakers were instructed to name digits in their L1 or L2 according to the color of the cue. The ERPs related to the cue and the stimulus for two presentation sequences were measured. In the stimulus-cue sequence, the analysis that was time-locked to cues revealed a reversed switch cost as early as 220 ms after the cue onset; furthermore, a switch cost was shown in L1 with a late stage post-cue onset. The results suggested that when language selection occurred after lemma activation, the switch costs mainly occurred at the lemma selection stage. In the cue-stimulus sequence, the analysis that was time-locked to cues did not reveal significant main effects of switching, whereas the ERPs that were time-locked to digits yielded a switch cost, again indicating that switch costs mainly occurred at the lemma selection stage rather than at the language task schema competition stage. Overall, our results indicated that when bilinguals read digits aloud in the language switching task, switch costs mainly occurred at the lemma selection stage.